From trauma to natural birth: development of natural birth perception scale - Bülez, Aysel; Sayıner, Fatma Deniz; Öztürk, Duygu Murat (Acta Scientiarum. Health Sciences, 2024)
This study was conducted in order to develop a scale regarding ‘Natural Birth Perception of the Pregnants in the Last Trimester’. The study was conducted cross-sectionally between March 1 and May 1, 2019. The universe of the study consisted of pregnant women (N: 356) above the age of 18 and in the third trimester. In the study, factor analysis was conducted to determine the construct validity of the Natural Birth Perception Scale. The internal reliability coefficient of the test was found to be quite high (cronbach alpha, 89). As the score obtained from the scale increases, the perception of natural birth increases positively. The Natural Birth Perception Scale can be used safely in measuring the natural birth perception of pregnant women.